Experimental observables of shape phase transition from vibrational to Gamma- unstablExperimental observables of shape phase transition from vibrational to Gamma- unstable in the odd and even nucleie in the odd and even nuclei - M. Ghapanvari; M. Sayedi (مجله علوم و فنون هسته‌ای, 2022)
In this paper, Quantum Phase Transition (QPT) for the Xenon (122-132Xe) isotopes chain in the frameworks of the IBM-1 and IBFM-1 is considered. In order to study the QPT in this chain, we have used the observables such as: binding energy, two neutron separation energy, Alpha decay energy, R4/2 and B(E2). The results show that transitional nuclei in the regions of  for even-even isotopes and  for even-odd isotopes are 130Xe and 127Xe respectively.